2006
DOI: 10.1007/s11095-005-9371-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acid and Lactone Forms of Eight HMG-CoA Reductase Inhibitors on CYP-Mediated Metabolism and MDR1-Mediated Transport

Abstract: We showed the difference between the acid and lactone forms in terms of drug interaction. The lipophilicity could be one of the important factors for inhibitory effects. In the case of statins, it is important to examine the effects of both forms to understand the events found in clinical settings, including the pleiotropic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 49 publications
2
64
0
Order By: Relevance
“…Based on available data, pravastatin is unlikely to be a substrate of CYP3A4 or CYP2C9; the co-administration of CYP3A4 inhibitors (i.e., verapamil, mibefradil, itraconazole, clarithromycin, and grapefruit juice) or CYP2C9 inhibitor (i.e., fluconazole) had no significant effect on the pharmacokinetics of pravastatin (Fukazawa et al 2003;Jacobson 2004;Kantola et al 2000). Additionally, in vitro inhibition profiles of major human drug metabolizing CYP isoenzymes (i.e., CYP2C8, CYP2C9, CYP2C19, CYP3A4 and CYP3A5) by pravastatin showed that both acid and lactone forms of pravastatin had minimal inhibitory effects on metabolic activities of all five CYP isoenzymes with IC 50 values [100 lM (Sakaeda et al 2006). Taking these into consideration, increased AUC and decreased CL t /F of olmesartan in the co-administration phase are unlikely to result from the inhibition of CYP-mediated metabolism of olmesartan by pravastatin.…”
Section: Resultsmentioning
confidence: 98%
“…Based on available data, pravastatin is unlikely to be a substrate of CYP3A4 or CYP2C9; the co-administration of CYP3A4 inhibitors (i.e., verapamil, mibefradil, itraconazole, clarithromycin, and grapefruit juice) or CYP2C9 inhibitor (i.e., fluconazole) had no significant effect on the pharmacokinetics of pravastatin (Fukazawa et al 2003;Jacobson 2004;Kantola et al 2000). Additionally, in vitro inhibition profiles of major human drug metabolizing CYP isoenzymes (i.e., CYP2C8, CYP2C9, CYP2C19, CYP3A4 and CYP3A5) by pravastatin showed that both acid and lactone forms of pravastatin had minimal inhibitory effects on metabolic activities of all five CYP isoenzymes with IC 50 values [100 lM (Sakaeda et al 2006). Taking these into consideration, increased AUC and decreased CL t /F of olmesartan in the co-administration phase are unlikely to result from the inhibition of CYP-mediated metabolism of olmesartan by pravastatin.…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that rosuvastatin may be modified by the CYP3A5 enzyme and that the metabolite either has increased ability to inhibit HMG-CoA reductase or is of a similar inhibitory activity but less readily excreted from the hepatocyte. It has previously been reported that unlike the acid form of rosuvastatin, the lactone form is a good substrate of the CYP3A4/3A5 enzymes, 37,38 and that itraconazole, an inhibitor of CYP3A4, leads to modest increases in rosuvastatin plasma concentrations. 39 Furthermore, atorvastatin, a closely related molecule, has previously been reported to undergo modification by the CYP3A4/3A5 enzymes and yet still retain HMG-CoA reductase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…12 Unlike other statins, pitavastatin does not undergo extensive metabolism by cytochrome P450 isoenzymes, and hence the potential for interactions with drugs that are metabolized by cytochrome P450 is low. 12,13 A 12-week, randomized, double-blind trial in patients at high risk of CHD showed that pitavastatin 4 mg was statistically non-inferior to simvastatin 40 mg for the reduction of LDL-C concentrations, and provided larger increases in HDL-C (6.8% vs. 4.5%; P=0.083) and reductions in triglycerides (-19.8% vs. -14.8%; P=0.044) than simvastatin treatment. 14 …”
Section: Introductionmentioning
confidence: 99%